Penanganan Impor Suku Cadang pada Perusahaan Perdagangan Alat Berat di Indonesia - Kadarisman, Muh; Bestari, Viqy Esha; Setiawan, Edhie Budi; Rahardjo, Sri; Handayani, Sri (Institut Transportasi dan Logistik Trisakti, 2025)
The main problem of this research is that there was an import customs settlement process that still requires the results of a surveyor company certified by the government to be attached to the Bonded Logistics Center warehouse outside the port, increasing the waiting time.This research analyzes the import handling process, government policies, and customs compliance in handling heavy equipment spare parts.This research used a qualitative analysis approach with purposive sampling with 10 informants from various companies.The research findings are that there was still a lack of government role in increasing the effectiveness of handling the import process of heavy equipment spare parts at the heavy equipment trading company, due to weaknesses in determining import restrictions.Steel heavy equipment spare parts were invalid because heavy equipment spare parts were made in factories in the home country of the heavy equipment maker. It is difficult to transfer technology to domestic production because the price of fabrication machines requires quite a high investment and high technical specifications. The company also experienced losses in terms of transportation costs